Algo más sobre la nota de posesión de la versión árabe de la Colección canónica y la datación del códice 1623 de la Real Biblioteca de El Escorial - Monferrer-Sala, Juan Pedro (Isidorianum, 2024)
The versified note that appears at the end of book VII, fol. 333r, in al-Qānūn al-Muqaddas, "the Holy Canon", is of great relevance in order to know to which bishop the codex belonged, and the time in which the text was translated from Latin into Arabic. In this article we give a series of explanations and arguments about these two issues: which bishop was the owner of the text and when the translation of the Latin original could be made. A final allusion about its possible translator is added.